Characterization of Growth Morphology and Pathology, and Draft Genome Sequencing of Botrytis fabae, the Causal Organism of Chocolate Spot of Faba Bean (Vicia faba L.) - Lee, Robert C.; Farfan-Caceres, Lina M.; Debler, Johannes W.; Syme, Robert A. (Frontiers in Microbiology, 2020)
Abstract Chocolate spot is a major fungal disease of faba bean caused by the ascomycete fungus, Botrytis fabae. B. fabae is also implicated in botrytis grey mould disease in lentils, along with B. cinerea. Here we have isolated and characterised two B. fabae isolates from chocolate spot lesions on faba bean leaves. In plant disease assays on faba bean and lentil, B. fabae was more aggressive than B. cinerea and we observed variation in susceptibility among a small set of cultivars for both plant hosts. Using light microscopy, we observed a spreading, generalised necrosis response in faba bean towards B. fabae. In contrast, the plant response to B. cinerea was localised to epidermal cells underlying germinated spores and appressoria. In addition to the species characterisation of B. fabae, we produced genome assemblies for both B. fabae isolates using Illumina sequencing. Genome sequencing coverage and assembly size for B. fabae isolates, were 27x and 45x, and 43.2 Mb and 44.5 Mb, respectively. Following genome assembly and annotation, carbohydrate-active enzyme (CAZymes) and effector genes were predicted. There were no major differences in the numbers of each of the major classes of CAZymes. We predicted 29 effector genes for B. fabae, and using the same selection criteria for B. cinerea, we predicted 34 putative effector genes. For five of the predicted effector genes, the pairwise dN/dS ratio between orthologs from B. fabae and B. cinerea was greater than 1.0, suggesting positive selection and the potential evolution of molecular mechanisms for host specificity in B. fabae. Furthermore, a homology search of secondary metabolite clusters revealed the absence of the B. cinerea phytotoxin botrydial and several other uncharacterised secondary metabolite biosynthesis genes from B. fabae. Although there were no obvious differences in the number or proportional representation of different transposable element classes, the overall proportion of AT-rich DNA sequence in B. fabae was double that of B. cinerea.